MARKETING STRATEGY OF PT INDUSTRI JAMU AND SIDOMUNCUL PHARMACY TBK IN REACHING THE INTERNATIONAL MARKET - Andi Dewi Angreyani; Muh Al Fatah AP; Andini Ramadani (Journal Management & Economics Review (JUMPER), 2023)
As the business world evolves with intense competition, consumers are becoming more discerning in their decision making when choosing high quality goods at the desired cost in order to receive the greatest value from their purchase. So that an international marketing strategy is needed at PT Sido Muncul. It is hoped that this research can become a reference and description of a company in developing marketing strategies that are international markets. This study examines the international marketing strategy at PT Sido Muncul. It is hoped that this research can become a reference and description of a company in developing marketing strategies that are international markets. Data analysis techniques use interactive model analysis which involves data reduction, data presentation, and drawing conclusions. The results show that Sido Muncul continues to develop its products, increasing the reach of target customers, product variants, and production capacity. Initially, PT Sido Muncul’s target market is in Export destinations are Indonesian citizens and foreign tourists who have been to Indonesia. However, as time goes by, PT Sido Muncul's products are increasingly in demand by local people in export destination countries. The strategy used is to build overseas branches in the Philippines and branches in Nigeria, product development, and expansion of domestic distribution.